Mechanistic-based field evaluation of pavement foundation - Nazarian, Soheil (2009)
For the last few decades, practitioners have understood the importance of the properties of pavement foundation layers on the performance of rigid and flexible pavements. With the pavement community’s widespread interest in implementing a new mechanistic empirical pavement design program (ME-PDG), the importance of accurately quantifying the stiffness and thickness of the foundation layers has become even more critical.